EMOTION ANALYSIS IN SYLVIA PLATH POETRY “DADDY” - Siahaan, Safnidar (Universitas Riau Kepulauan, 2015)
In this analysis, the writer chooses poetry entitled “Daddy” written by Sylvia Plath. The aim of this analysis is to find emotion expressed in the poetry. The result of this analysis conclude that feeling of sadness often expressed in this poem because the poem describes the grief and suffering experienced during the Nazy German. The situation made Plat depression and despair, but she tried to get up and running her life for victory. Based on this analysis, there are emotions showing sadness, disgust, anger, anxiety, happiness, guilt, and love. In collecting the data, the writer applies the method and technique of observation log. Data taken from the poem “Daddy” and analyzed by using the theory of psychology of emotion discovered by Minderop (2003)